Process for the Synthesis of Carbamate of Cefpodoxime Proxetil - Gupta, Ashish; Lakshminarayana Sharma, P.; Muralikrishna, Dantu (Asian Journal of Chemistry, 2010)
Carbamate of cefpodoxime proxetil is prepared by reaction of cefpodoxime proxetil with isopropyl chloroformate in presence of N-methyl morpholine.